Kelayakan Pemutus Tenaga 150 KV Berdasarkan Uji Tahanan Isolasi Dan Tahanan Kontak - Rezyan, Rizky Fiqliyarli; Arnisa Stefanie (EPIC Journal of Electrical Power Instrumentation and Control, 2024)
The circuit breaker is a crucial component in the electric power system infrastructure that requires insulation resistance and contact resistance testing to ensure its safe and effective performance. The purpose of this research is to assess the success of a 150 kV circuit breaker using insulation resistance and contact resistance tests as indicators. Data collection methods include expert interviews, literature review, and direct observation of the tested circuit breaker. Insulation resistance testing is conducted using insulation testing equipment, while contact resistance is measured using an MOM 690 test device. The research results indicate that the insulation resistance and contact resistance values of the 150 kV circuit breaker meet the standards set by the manufacturer. It is recommended to schedule periodic testing to ensure that the equipment continues to function properly. The importance of insulation resistance and contact resistance testing in maintaining the safe and effective performance of the circuit breaker is also emphasized in this study. Therefore, this research provides a comprehensive understanding of the importance of insulation resistance and contact resistance testing in maintaining the reliability of circuit breakers and preventing potential damage and accidents.